Use of vasoactive medications in pregnancy and the risk of stillbirth among birth defect cases. Issue 8 (2nd March 2022) - Kerr, Stephen; Heinke, Dominique; Yazdy, Mahsa M.; Mitchell, Allen A.; Darling, Anne Marie; Lin, Angela; Nestoridi, Eirini; Werler, Martha M.; ,
Abstract: Background: Many previous studies have identified risk factors for stillbirth, but few examine stillbirth among pregnancies affected with birth defects. Because many hypothesized etiologies of stillbirth work through vascular pathologies of the placenta, we examined maternal use of vasoactive medications in relation to stillbirth among pregnancies affected with birth defects. Methods: Data were analyzed from the National Birth Defects Prevention Study (1997–2011). We examined use of nonsteroidal anti‐inflammatory drugs (NSAIDs), decongestants, short‐ or long‐acting beta‐agonists (SABA/LABA), and antihypertensive medications in relation to pregnancies affected by birth defects ending in stillbirth compared to live birth. Associations were measured with odds ratios (ORs) for early pregnancy use and hazard ratios (HRs) for time‐varying late pregnancy use. Results: Among all birth defects ( n = 12, 394), the risk of stillbirth was associated with use of antihypertensive medications in early (odds ratio [OR]: 1.8; 95% confidence interval [CI]: 1.0, 3.1) and late pregnancy (HR: 2.0; 95% CI: 1.1, 3.6). Other vasoactive medications were not associated with increased risk of stillbirth. Of 27 specific defect groups, increased risks were observed for only one medication/defect pair: early decongestant use was more common among mothers of stillbirth versus live birth cases with spina bifida (OR: 2.4; 95% CI: 0.9, 6.5). Conclusion: This exploratory analysis of vasoactive medication use suggests that use of NSAIDs, decongestants, and SABA/LABA is not associated with increased risk of stillbirth among pregnancies affected with birth defects. Our finding of increased risks associated with antihypertensive medication use raises questions of confounding by indication, which we were not able to fully address.